Metode Ijtihad dalam Islam - Indra Kurniawan, Muhamad; Rojudin, Rojudin; Sucipto, Imam (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2024)
This research aims to explain the method of ijtihad in Islam. The research uses qualitative methods by collecting data that can support this research both primary and secondary data. The results and discussion of this research include the definition, legal basis, position and function, object, and division of ijtihad, as well as the requirements of people doing ijtihad (mujtahid). The conclusions of this research are: (1) Ijtihad is: the process of earnest work with all the efforts of Islamic law experts (faqih - jurists) in exploring and determining the laws of sharia, (2) The legal basis for ijtihad is QS. An-Nisa: 105, QS. Al-Anbiya: 78-79, QS. As-Syura: 38, several hadiths of the prophet and the atsar of Caliph Umar, (3) The position and function of ijtihad is a means for Muslims to find laws and solutions to developing problems, (4) The object of ijtihad is zhanni matters, as well as laws that have no nashnya and ijma of the scholars, (5) The division of ijtihad is: fardi ijtihad and jama'i ijtihad, (6) The requirements for mujtahid are understanding: Al-Qur'an and sunnah, ijma, ikhtilaf, ushul fiqh, qiyas, Arabic language, maqashidus sharia, and reality, and have credibility. Keywords: ijtihad, method, mujtahid